Not‐in‐trial simulation I: Bridging cardiovascular risk from clinical trials to real‐life conditions - Chain, Anne S. Y.; Dieleman, Jeanne P.; Noord, Charlotte; Hofman, Albert; Stricker, Bruno H. Ch; Danhof, Meindert; Sturkenboom, Miriam C. J. M.; Della Pasqua, Oscar (British journal of clinical pharmacology, 2013)
Aims The assessment of heart rate‐corrected QT (QTc) interval prolongation relies on the evidence of drug effects in healthy subjects. This study demonstrates the relevance of pharmacokinetic–pharmacodynamic (PKPD) relationships to characterize drug‐induced QTc interval prolongation and explore the discrepancies between clinical trials and real‐life conditions. Methods d,l‐Sotalol data from healthy subjects and from the Rotterdam Study cohort were used to assess treatment response in a phase I setting and in a real‐life conditions, respectively. Using modelling and simulation, drug effects at therapeutic doses were predicted in both populations. Results Inclusion criteria were shown to restrict the representativeness of the trial population in comparison to real‐life conditions. A significant part of the typical patient population was excluded from trials due to weight and baseline QTc interval criteria. Relative risk was significantly different between sotalol users with and without heart failure, hypertension, diabetes and myocardial infarction (P < 0.01). Although drug effects do cause an increase in the relative risk of QTc interval prolongation, the presence of diabetes represented an increase from 4.0 [95% confidence interval (CI) 2.7–5.8] to 6.5 (95% CI 1.6–27.1), whilst for myocardial infarction it increased from 3.4 (95% CI 2.3–5.13) to 15.5 (95% CI 4.9–49.3). Conclusions Our findings show that drug effects on QTc interval do not explain the observed QTc values in the population. The prevalence of high QTc values in the real‐life population can be assigned to co‐morbidities and concomitant medications. These findings substantiate the need to account for these factors when evaluating the cardiovascular risk of medicinal products.